2020
DOI: 10.3390/microorganisms8081174
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Chronological Microbiota Changes in a Rat Apical Periodontitis Model

Abstract: Apical periodontitis caused by microbial infection in the dental pulp is characterized by inflammation, destruction of the pulpal and periradicular tissues, and alveolar bone resorption. We analyzed the chronological changes in microbiota using a pyrosequencing-based approach combined with radiologic and histopathologic changes in a rat apical periodontitis model. During the three-week observation, the pulp and periapical area showed a typical progress of apical periodontitis. A total of 27 phyla, 645 genera, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
2
7
0
2
Order By: Relevance
“…As shown in Figure 5 , Proteobacteria , Firmicutes , Bacteroidetes , and Actinobacteria were dominant phyla in both ligated molars tied with oil-immersed and oil-free ligatures. This population is similar to microbiota found in the analysis of saliva, pulp chamber, and root apex [ 42 ] and is often identified in healthy subjects [ 43 ]. However, our results demonstrated that the microbial community of ligated molars changed after SM oil treatment.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As shown in Figure 5 , Proteobacteria , Firmicutes , Bacteroidetes , and Actinobacteria were dominant phyla in both ligated molars tied with oil-immersed and oil-free ligatures. This population is similar to microbiota found in the analysis of saliva, pulp chamber, and root apex [ 42 ] and is often identified in healthy subjects [ 43 ]. However, our results demonstrated that the microbial community of ligated molars changed after SM oil treatment.…”
Section: Discussionsupporting
confidence: 69%
“…With bacteria known to be the major factor inducing bone loss in periodontitis [ 28 , 30 ] and the ability to accumulating commensal microbial biomass to trigger a switch from homeostasis to inflammation [ 41 ], SM oil’s anti-bacterial properties suggest the material as a potential periodontitis inhibitor. Increased microbial diversity is characteristic of disease development in the root apex, and the increased specific bacterial communities are closely associated with disease progression [ 42 ]. The heatmap in Figure 4 shows that samples tied with SM oil-immersed ligatures exhibited lower diversity at both family and genus levels ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gemella sanguinis Gram+ facultative anaerobe periodontal pathogen; affects the periodontal health status and is prevalent in refractory periodontitis; in subgingival niche [5,37] Haemophilus parainfluenzae Gram− facultative anaerobe significantly more prevalent in periodontal health than periodontitis [37] Lactobacillus Gram+ anaerobe associated with carious lesions, anticaries potential, can inhibit tooth decay by limiting growth and virulence properties of Streptococcus mutans", dominant genera in the pulp chamber of apical periodontitis (rat model) [45,[48][49][50] Lautropia mirabilis Gram− facultative anaerobe localized on the back of the tongue, significantly more prevalent in periodontal health than periodontitis [37,51] Megaspahera elsdenii Gram− anaerobe one of the most abundant genera in the native biofilm…”
Section: Genus and Species Gram Type Growth Conditions Clinical Relevance Referencesmentioning
confidence: 99%
“…Some important periodontal pathogens, such as Tannerella forsythia , that have never been cultivated from infected root canals were detected in AP ( Siqueira and Rôças, 2017 ). Furthermore, next-generation sequencing can aid in data analysis for thousands of different amplicons, rather than just individual or multiple samples, yielding enormous datasets, thereby offering more profound insight into AP ( Park et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%